The Effect of Dried Blood Rumen Content Mixture (D BRCM) on Carcass Characteristics of SASSO C44 Broiler Chicks - Yitbarek, Melkamu Bezabih; Tamir, Berhan; Mengistu, Ashenafi (European Scientific Journal, ESJ, 2016)
The experiment was conducted to evaluate the effect of dried bloodrumen content mixture (DBRCM) on carcass characteristics of broiler chicks to replace soybean meal (SBM). A total of 225 unsexed day old broiler chicks (SASSO C44) were randomly distributed to five dietary treatment groups in a completely randomized design. Each treatment was replicated thrice with 15 birds per replicate. The experimental diets were formulated to contain 100%SBM+0%DBRCM (T1), 80%SBM+20% DBRCM (T2),60%SBM+ 40% DBRCM (T3), 40%SBM+60% DBRCM(T4) and 20%SBM+80% DBRCM (T5) in 56 days of age. At the end of the experiment, two male and two female birds per replicate were used to determine carcass characteristics. The result revealed that the edible carcass yield ranged from 977.9-1159.3g. The dressing percentage based on the edible carcass weight was 63.9 % (T1), 66.6 % (T2), 65.4 (T3), 64.2% (T4) and 63.1% (T5). There was no a significant difference (P>0.05) in both edible carcass yield and its dressing percentage. The commercial carcass weight was 937.4g (T1), 984.7g (T2), 962.0g (T3), 925.0g (T4) and 833.1g (T5) and the dressing percentage was 54.9%, 56.6%, 55.3%, 53.7% and 53.7% for T1, T2, T3, T4 and T5, respectively. Significant difference (P>0.05) was not observed in commercial carcass yield and its dressing percentage among the treatment groups. There was no a statistical marked difference (P>0.05) in total nonedible offal and edible offal. Females had more (P<0.05) breast meat than that of males. The abdominal fat and abdominal fat percentage were not significantly influenced (P>0.05) by a diet containing DBRCM. However, abdominal fat and its fat percentage were higher (P<0.05) in females than males. Based on this result, it could be concluded that DBRCM can replace soybean meal up to 80% substitution level without any adverse effect on carcass characteristics.